Reliable and scalable tactical networks: A systematic literature review on routing protocols in mobile ad hoc networks (MANET) - Nikkola, Joona (My University, 2025)
Tactical environments are challenging for wireless communication. The area of operation lacks infrastructure while the operations require reliable communications and scalable networks. Mobile ad hoc networks (MANET) is a solution to infrastructure-less networking. MANETs are used by units from the military, the police, and the border security, along with search and rescue teams and other similar government agencies. There is overlapping terminology in infrastructure-less networking but this thesis focuses on general MANETs. There is a deficiency of review articles about general MANETs applicable to tactical communications in recent years. In this thesis we conducted a systematic literature review on general MANETs. 226 papers were reviewed from 2017 to 2024. We aimed to find research trends and focused on novel networking protocols In this thesis we found that the scientific community is moving away from MANETs in favour of other ad hoc technologies such as wireless sensor networks and vehicle born MANETs. Reactive routing has seen especially drastic decrease during the observation period. Similarly traditional algorithms have lost interest to machine learning algorithms and meta-heuristic algorithms which have shown increase in the observation period. We found that protocols increasingly use additional metrics in routing decisions. These metrics include energy, delay, congestion, quality of service, and physical location. The future correlation of ad hoc networks to tactical networks needs to be studied further. This thesis does not describe the effectiveness of the found routing methods, and they need to be studied further.
Keywords: tactical MANET, general MANET, routing protocol, SLR, systematic literature review